Simulador de Tempo Real para Sistemas Dinâmicos em FPGA - Silva, Sergio Natan (2016)
The development of new algorithms embedded for automation and control of industrial equipment usually require the use of real-time testing . However, the equipment required is often expensive, which means that such tests are not viable. This work aims at the development of an embedded platform in Field Programmable Gate Array (FPGA) for real-time simulation of dynamic systems associated with industrial plants. The platform called Simulator Real-Time for Dynamic Systems in FPGA (STRSD-FPGA) can be applied in industrial and academic settings. In industry the STRSD-FPGA can be used in optimizing and tuning of embedded control algorithms. In the academic sphere, will be used in research on new embedded solutions for the field of automation and control, as well as a support tool to undergraduate teaching and graduate in the development of embedded control systems projects. The simulator may, further, enable the acceleration of the simulation for cases of very slow dynamic systems, enabling a reduction in the total simulation time.